Methodological narrative review: Tools to measure fruit and vegetable consumption among toddlers ; challenges of measurement tools; variations in serving sizes and food preparation methods - Omar Alshukri, Amal (Libyan Journal of Medical and Applied Sciences, 2026)
Background/Rationale: Measurement of the consumption of fruit and vegetable accurately in toddlers is crucial for evaluating interventions to prevent obesity and promote healthy eating habits. Nevertheless, significant methodological limitations persist due to proxy reporting, variability in serving sizes, and diverse food preparation methods. Objectives: To assess the tools currently used to measure fruit and vegetable consumption among toddlers, identify challenges associated with measurement accuracy, and examine how variability food preparation methods and portion size impact assessment validity. Methods: A narrative review was conducted using systematic database searches of PubMed/MEDLINE, Scopus, and Web of Science for peer-reviewed studies published earlier and up to date. Search terms combined population descriptors (toddlers, young children, 1-3 years), dietary assessment methods (FFQs, 24-hour recalls, biomarkers, digital tools), and contextual factors (portion size, food preparation). Results: Conventional nutritional assessment techniques, such as FFQs and 24-hour recalls, are nevertheless vulnerable to proxy reporting mistakes, social desirability, and recollection bias. Digital photography and mobile applications are examples of emerging technologies that have the potential to enhance things but still need more testing. Skin carotenoid measurement is an example of an objective biomarker that shows potential as a substitute for validation problems in young infants. Significant variation in serving sizes and food preparation techniques (such as purees and mixed dishes) also significantly affects measurement accuracy and restricts cross-study comparisons. Conclusions: Measuring toddlers’ fruit and vegetable consumption is still challenging, despite advancements in dietary assessment methods. The most effective approaches must balance accuracy, feasibility, and burden while taking developmental characteristics into account. To increase measurement accuracy and intervention evaluation, future research should focus on developing age-appropriate technological solutions, standardizing portion size estimation, improving proxy-report methods, and validating objective biomarkers.